1996
DOI: 10.1038/bjc.1996.617
|View full text |Cite
|
Sign up to set email alerts
|

Interphase cytogenetics of prostate cancer: fluorescence in situ hybridisation (FISH) analysis of Japanese cases

Abstract: Summary No numerical aberration of chromosomes that might be specific for prostate cancer has so far been established. We used fluorescence in situ hybridisation (FISH) with centromere-specific probes for chromosomes 7, 8, 17, X and Y to establish the distribution of centromere copy numbers in frozen-stored or freshly prepared samples of benign prostate hypertrophy (BPH) and to detect numerical aberrations of these chromosomes in 28 prostate cancers from Japanese men. There was no significant difference in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Gains of chro- In particular, gain of chromosome 7 and/or 8 has been reported to be one of the most common numerical aberrations (2.9-66.0%, and 5.7-66.7%, respectively) and is associated with aggressive tumor behavior in prostate cancers [8,9,20,21,24]. Gain of chromosome X has also been recently reported in 40.0-45.7% of prostate cancers [8].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gains of chro- In particular, gain of chromosome 7 and/or 8 has been reported to be one of the most common numerical aberrations (2.9-66.0%, and 5.7-66.7%, respectively) and is associated with aggressive tumor behavior in prostate cancers [8,9,20,21,24]. Gain of chromosome X has also been recently reported in 40.0-45.7% of prostate cancers [8].…”
Section: Discussionmentioning
confidence: 95%
“…The c-myc gene encodes a DNA binding protein that is reported to be associated with cell proliferation [17] and programmed cell death [18,19]. Several cytogenetic studies in Western countries have suggested that gain of chromosome 8 and amplification of the c-myc gene are potential markers of prostate cancer progression [8,9,14,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…T u m o r Mostofi grade was strongly associated with chromosome copy number for chromosomes 7 Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…Satoru Takahashi et al, 13 reported that numeric changes of chromosomes 7, 8, X, and Y are common in prostate carcinoma. H Matsuura et al, 14 found in his study that out of 28 prostate cancers, the most common aberration in prostate cancers was a gain of chromosome 8 (57%), with numerical aberration of chromosome 7 being the second most frequent anomaly (50%). Robert B. Jenkins et al, 15 studied 25 prostate specimens, of which six tumours had no apparent anomaly for any chromosome 7 probe.…”
Section: Discussionmentioning
confidence: 95%